(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Fatma, Mallawa A, Najamuddin, Zainuddin M, Ayyub FR. 2022. Biological aspects of brown-marbled grouper (Epinephelus fuscoguttatus) from Taka Bonerate National Park, District of Selayar Islands, South Sulawesi, Indonesia. Biodiversitas 23: 1140-1153. Knowledge regarding biological aspects of fishes such as the brown-marbled grouper can provide important information for fisheries management. This research was conducted from February 2020 to February 2021 to determine the length-weight relationship, condition factor, gonad maturity stage and spawning pattern, size at first maturity and feeding habits of brown-marbled groupers in Taka Bonerate National Park. The sample caught comprised 1042 brown-marbled groupers with a total length (TL) range of 23-97 cm and a weight range of 0.5-17.6 kg. The length-weight equation was W: 0.0001?L2.5955 (R²: 0.8935). For male brown-marbled grouper (n: 569), TL range was 47-97 cm, weight range 1.65-17.60 kg, regression equation W: 0.0002?L2.4731 (R²: 0.7716), condition factor range 0.56-2.36 (mean 1.236±1.019), and length at first maturity 66.34 cm. For female brown-marbled grouper (n: 473) TL range was 23-73 cm (mean 46.84 cm), weight range 0.50-6.6 kg (mean 2.23 kg), regression equation W: 0.0007?L2.1057 (R²: 0.7416), condition factor range 0.55-2.17 (mean 1.225±1.018), and length at first maturity 45.43 cm. The growth pattern was negative allometric with regression coefficient b < 3 for both sexes separately and combined. The majority of both male and female fish caught had mature gonads with indications of a partial spawning pattern. The fish diet was carnivorous, predominantly piscivorous (74%), with gut contents comprising 64% unidentified fish and 26% unidentified decapod crustaceans. Over-exploitation of fish can cause negative impacts on populations, so the relationship between length and weight, condition factors and maturity level gonad of fish can be used in fisheries management.